Reconstructing Criminal Law To Distinguish Administrative Errors From Village Fund Corruption - Sari Darniati; Faizin Sulistio; Harun Al Rasyid (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study examines the reconstruction of Indonesian criminal law governing Village Fund management to establish clear legal boundaries between administrative misconduct and corruption offences. Using normative legal research with statutory, conceptual, and case approaches, the study analyses the Village Law, Government Administration Law, Anti-Corruption Law, and relevant Supreme Court decisions. The research proposes an integrated Administrative–Criminal Boundary Model requiring administrative screening, assessment of mens rea, abuse of authority, unlawful benefit, and actual state financial loss before criminal prosecution. The model strengthens legal certainty, prevents over-criminalization of village officials acting in good faith, and improves proportional anti-corruption enforcement.